Current Approaches to the Abnormal Toxicity Test - N. P. Neugodova; E. O. Stepanyuk; G. A. Sapozhnikova; E. I. Sakanyan; M. S. Ryabtseva (Регуляторные исследования и экспертиза лекарственных средств, 2020)
For over 60 years, the Abnormal Toxicity Test (ATT) has been used as an important tool in safety control of some parenteral and veterinary products made from biological materials. In 2017, some of the members of the Pharmacopoeial Committee of the Eurasian Economic Union (EAEU) proposed not to include the ATT in the draft monographs of the EAEU Pharmacopoeia based on the decision of the European Pharmacopoeia Commission to suppress the test. However, this may not be achieved in Russia at this point, because some production sites that manufacture medicinal products for human and veterinary use have not fully implemented GMP principles yet. The main aim of the ATT is to detect any toxicity above the pre-determined acceptable level. The unacceptable toxicity levels can manifest themselves in higher mortality rates or unexpected intoxication effects in laboratory animals. This test makes it possible to detect abnormal (high) toxicity of a medicinal product which may be associated with degradation products or undesirable impurities resulting from changes of the production technology, which are not mentioned in specification documents related to production, transportation, and storage. In 2016—2017 12 batches of veterinary products, including vaccines and sera, were found to be noncompliant, and the Federal Service for Surveillance in Healthcare rejected 16 batches of medicinal products in 2016—2019. The aim of the study was to analyse current approaches to the ATT in the Russian and foreign pharmacopeias, and to develop a programme for phasing out the ATT use depending on the nature and pharmacological properties of medicinal products. Comparative analysis of the monographs of the world leading pharmacopeias showed that the State Pharmacopoeia of the Russian Federation has the most stringent test conditions. As an alternative to suppressing the ATT the authors suggest a phased approach to reduce the use of this test. They determined groups of medicinal products whose pharmacological properties allow for the suppression of the test. The proposed approach to phasing out the use of ATT will make it possible to use the test effectively and reduce the number of performed tests, but will still ensure drug safety. The suppression of the ATT can not be achieved without a comprehensive detailed research by quality control specialists and further discussion by all interested parties.